2016
DOI: 10.1038/npp.2016.104
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Prefrontal–Amygdala Recruitment to Angry and Happy Expressions in Pediatric Posttraumatic Stress Disorder

Abstract: The neural substrates of pediatric posttraumatic stress disorder (PTSD) remain incompletely understood, but likely involve abnormal function and development of emotion processing circuitry. Valence-specific and age-related abnormalities during emotion processing have not been elucidated. We examined implicit emotional face processing in pediatric PTSD, predicting abnormalities specific to threat-related emotion. Youth (ages 8-18 years) with PTSD (n = 25) and healthy youth (n = 28) completed a dynamic emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 63 publications
6
54
1
1
Order By: Relevance
“…To this end, we examined amygdala functional connectivity during emotion processing in our sample of youth with PTSD. Notably, we found that youth with PTSD exhibit reduced coupling between the amygdala and rACC/dmPFC, which was further linked to PTSD severity [35,57]. These findings also agree with studies showing an inverse relationship between PTSD symptoms and amygdala-rACC coupling in adolescent sexual assault victims [59].…”
Section: Functional Brain Abnormalities During Emotion Processing In supporting
confidence: 88%
See 3 more Smart Citations
“…To this end, we examined amygdala functional connectivity during emotion processing in our sample of youth with PTSD. Notably, we found that youth with PTSD exhibit reduced coupling between the amygdala and rACC/dmPFC, which was further linked to PTSD severity [35,57]. These findings also agree with studies showing an inverse relationship between PTSD symptoms and amygdala-rACC coupling in adolescent sexual assault victims [59].…”
Section: Functional Brain Abnormalities During Emotion Processing In supporting
confidence: 88%
“…With regard to mid/dACC activation, earlier studies found no differences in activation relative to TD youth [38,55,56]. On the other hand, we have found dACC hyperactivation to both threat pictures and emotional faces in our sample of youth with PTSD [35,57]. This is notable given that the dACC is hypoactive in adult PTSD [58].…”
Section: Functional Brain Abnormalities During Emotion Processing In contrasting
confidence: 43%
See 2 more Smart Citations
“…There is some evidence to suggest that processing of emotional valence itself is altered in PTSD, in particular for individuals who have suffered childhood maltreatment 102103 . Given our desire to understand the basic neuroscience of negative emotions, there has been considerable recent effort made to use modern optogenetic and chemogenetic tools to understand the coding of valence in the mouse brain subpopulations of neurons in the BLA 104 , central amygdala 105 , nucleus accumbens 106 and ventral tegmental area (VTA) 107 , and other regions appear to respond to the appetitive or aversive qualities of a stimulus, independent of its sensory features 10 .…”
Section: Altered Cognition and Moodmentioning
confidence: 99%